Efflux Pump-mediated Drug Resistance in Burkholderia - Podnecky, Nicole L.; Rhodes, Katherine A.; Schweizer, Herbert P. (Frontiers in Microbiology, 2015)
Several members of the genus Burkholderia are prominent pathogens. Infections caused by these bacteria are difficult to treat because of significant antibiotic resistance. Virtually all Burkholderia species are also resistant to polymyxin, prohibiting use of drugs like colistin that are available for treatment of infections caused by most other drug resistant Gram-negative bacteria. Despite clinical significance and antibiotic resistance of Burkholderia species, characterization of efflux pumps lags behind other non-enteric Gram-negative pathogens such as Acinetobacter baumannii and Pseudomonas aeruginosa. Although efflux pumps have been described in several Burkholderia species, they have been best studied in B. cenocepacia and B. pseudomallei. As in other non-enteric Gram-negatives, efflux pumps of the resistance nodulation cell division (RND) family are the clinically most significant efflux systems in these two species. Several efflux pumps were described in B. cenocepacia, which when expressed confer resistance to clinically significant antibiotics, including aminoglycosides, chloramphenicol, fluoroquinolones, and tetracyclines. Three RND pumps have been characterized in B. pseudomallei, two of which confer either intrinsic or acquired resistance to aminoglycosides, macrolides, chloramphenicol, fluoroquinolones, tetracyclines, trimethoprim, and in some instances trimethoprim+sulfamethoxazole. Several strains of the host-adapted B. mallei, a clone of B. pseudomallei, lack AmrAB-OprA and are therefore aminoglycoside and macrolide susceptible. B. thailandensis is closely related to B. pseudomallei, but non-pathogenic to humans. Its pump repertoire and ensuing drug resistance profile parallels that of B. pseudomallei. An efflux pump in B. vietnamiensis plays a significant role in acquired aminoglycoside resistance. Summarily, efflux pumps are significant players in Burkholderia drug resistance.